Food consumption patterns and food beliefs of the Gaddangs of Nueva Vizcaya - Sarmiento, Adorinda Monje (1999)
This study is a general description and analysis of the food consumption patterns and food beliefs of the Gaddangs in Nueva Vizcaya. Specifically, the study focused on their food intake patterns in terms of frequency, variety, combination and sequencing; socio-demographic and economic factors related to food variety; methods of cooking, preserving and storing food; and food beliefs in special occasions of the young and old, rural and urban Gaddangs. One hundred sixty six household heads from three Gaddang communities participated in the study. Results showed that of the almost 40 items in the food frequency checklist, only rice and sugar were consumed daily by majority of the households. Of the several food combinations in each meal there was one that stood out as the most common. The reported diets of the household heads were rated fair in terms of variety. Rice was eaten first in every meal. The variety of foods eaten by the household heads was not associated with age, educational attainment, occupation nor with household income and size. Several methods of cooking and preserving foods were employed by the households including using of bamboo tubes in cooking and meat preservation. In terms of food beliefs, the Gaddangs are found to eat and avoid certain foods on special occasions such as birthdays, weddings, burials, lenten season and during pregnancy and lactation. Food beliefs were very much a part of the culture of the Gaddangs. Some beliefs were shared in common by both the young and old Gaddangs and rural and urban Gaddangs. However, more older and rural Gaddangs had beliefs related to what foods to eat or avoid during special occasions and certain periods of the life cycle. There were more food beliefs during pregnancy and lactation compared to birthdays, weddings, lenten season, burials, and planting/harvesting season.